2020
DOI: 10.3390/biomedicines8110457
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a Risk Factor for Dementia and Alzheimer’s Disease

Abstract: Preventing the onset of dementia and Alzheimer’s disease (AD), improving the diagnosis, and slowing the progression of these diseases remain a challenge. The aim of this study was to elucidate the association between depression and dementia/AD and to identify possible relationships between these diseases and different sociodemographic and clinical features. In this regard, a case-control study was conducted in Spain in 2018–2019. The definition of a case was: A person ≥ 65 years old with dementia and/or AD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 80 publications
2
53
0
Order By: Relevance
“…Serum plasma profiles may serve as a potential predictive biomarker for the choice of antidepressants [ 123 ]. Foods, or fortified food products beneficial to physiological body functions, were proposed for the treatment of metabolic dysfunction in ageing neurodegenerative diseases [ 124 ]. In addition to biomolecules, any measurable indicators are important for risk, diagnosis, prognostic, and predictive biomarkers and interventional targets.…”
Section: Neurological Sciences’ Approach To Mood and Anxiety Disordersmentioning
confidence: 99%
“…Serum plasma profiles may serve as a potential predictive biomarker for the choice of antidepressants [ 123 ]. Foods, or fortified food products beneficial to physiological body functions, were proposed for the treatment of metabolic dysfunction in ageing neurodegenerative diseases [ 124 ]. In addition to biomolecules, any measurable indicators are important for risk, diagnosis, prognostic, and predictive biomarkers and interventional targets.…”
Section: Neurological Sciences’ Approach To Mood and Anxiety Disordersmentioning
confidence: 99%
“…Several studies have recently shown a strong association between metabolic disturbances and the development of anxiety-related disorders and poor cognitive outcomes (Avinun and Hariri, 2019;Ronan et al, 2019;van Duinkerken and Ryan, 2019), with higher rates of anxiety and depression found in overweight and obese people (Luppino et al, 2010;Gomes et al, 2019;James et al, 2020). Interestingly, both anxiety and depression are associated with an increased likelihood of developing AD (Becker et al, 2018;Canton-Habas et al, 2020).…”
Section: Neurological Consequences Of Obesity-related Derangements: Metabolic Risk Factors For Alzheimer's Diseasementioning
confidence: 99%
“…The serum plasma profiles may serve as a potential predictive biomarker for the choice of antidepressants [118]. A food or fortified food product beneficial to physiological body functions, were proposed for the treatment of metabolic dysfunction in ageing neurodegenerative diseases [119]. In addition to biomolecules, any measurable indicators are entitled for risk, diagnosis, prognostic, and predictive biomarkers and interventional targets.…”
Section: Other Relevant Biomarkers and Therapeutic Targetsmentioning
confidence: 99%